Influence of the Size and Mechanical Strength of Natural Diamond Grains in the Matrix of Diamond Tube Drills on Their Performances in the Drilling of Selected Nonmetallic Materials - Umansky, V. P.; Krasovskyy, V. P.; Bashchenko, O. O. (Powder metallurgy and metal ceramics, 2025)
Six diamond tube drills were fabricated by vacuum impregnation using cutting grains of natural diamonds of grade A1 with grain sizes of 250/200, 315/250, 500/400, 800/600, 1000/800, and 1200/1000 μm. For comparative analysis, three drills were produced with synthetic diamonds of grades AS32 500/400, AS400 315/250, and AS400 500/400 (DSTU 3292–95). To ensure reliable fixation in the tool body, diamond grains coated with molybdenum and copper were embedded in a Cu–15 wt.% Sn matrix with added fillers (5 wt.% ultrafine diamond powder of grade ASM 1/0 and molybdenum). The compressive strength of the diamond grains was evaluated. The paper presents results from comparative laboratory tests of the diamond drills in marble, granite, and silicon carbide-based abrasive stone. Performance characteristics—drilling speed and drill wear—were studied as functions of the natural diamond grade used. The drilling speed depended on the size of the diamond grains. The lowest drilling speeds (3.52, 6.83, and 23.1 mm/min for granite, marble, and abrasive stone) were observed in drills equipped with small (A1 250/200 μm) and weak (50 N) diamond grains. When larger (A1 1200/1000 μm) and stronger (350 N) diamond grains were used, the drilling speed increased significantly (by approximately 4, 3.2, and 3.8 times) to 14.07, 22.1, and 87.99 mm/min for granite, marble, and abrasive stone, respectively. The lowest drilling speed observed in granite with all tested drills was due to its high hardness, being approximately twice that of marble. However, despite even greater hardness of silicon carbide, forming the base of the abrasive stone, the drilling speed remained high. When marble was drilled with tools containing the smallest diamond grains (A1 250/200 μm), their wear amounted to 0.0139 g. For harder materials (granite and abrasive stone), tool wear increased significantly (by factors of 41 and 48), reaching 0.5701 and 0.6665 g. With increasing grain size and compressive strength of the natural diamond grains, drill wear decreased, by factors of approximately 8, 317, and 14 for marble, granite, and abrasive stone. The greatest reduction in wear was recorded for granite. As a result, drills equipped with large and strong diamond grains (A1 1000/800 and A1 1200/1000) exhibited similarly minimal wear in the drilling of marble and granite: 0.0036 and 0.0018 g for granite and 0.0035 and 0.0017 g for marble.